Hybridization between biomedicine and alternative medicine in COVID-19 care in a neo-rural population of Córdoba, Argentine - Santoro, Flavia Rosa; da Silva Chaves, Leonardo; Arias Toledo, Bárbara (Ethnobiology and Conservation, 2023)
We propose to investigate if the use and knowledge of medicinal plants and alternative medicine influence the adoption of biomedical strategies in dealing with COVID-19 - such as the use of masks, social isolation, and vaccination - in a context of a neo-rural population. We collected data through online questionnaires, using the Google Forms platform in the “Paravachasca Valley”, Córdoba, Argentine. The questionnaires, anonymous, contained multiple choice questions about attitudes and opinions concerning prophylactic strategies against COVID-19. To test whether the use or knowledge of medicinal plants is associated with trust in the efficiency and adoption of biomedical strategies, we used a chi-square test of independence. We saw that this neo-rural population does not differ from urban populations in terms of the proportion of people who deny biomedical strategies to prevent COVID-19. Furthermore, we verified that the knowledge about medicinal plants is related to distrust and reluctance to the adoption of the use of masks, social isolation, and vaccination. Also, our results suggest that alternative medicine users are afraid of the vaccine effects. In this plural medical context of a neo-rural population, belief in alternative medicines for the treatment of COVID-19 can be an obstacle to immunization programs.